POWER MODELLING OF L.C.D. DISPLAY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Now days most of embedded system used are battery operated. To predict the battery life, power consumption at various levels, like software and power taken by peripheral devices should be known in advance. The components of total power consumption are software power & power taken by peripheral devices these should be known to the designer. In this paper for prediction the modelling of L.C.D. by using statistical tools i.e. regression analysis. Here we must understand how much power required to display a particular character.